Challenges and Counteracting Strategies Including Optimum Health Service Practices for Frontline Nurses During the Mpox Outbreak and Futuristic Vision - Sirwan Khalid Ahmed RN, BSc, MSc; Eman A. Dabou RN, MSc, PhD; Fatma M. Ibrahim RN, MSc, PhD; Mona G. Mohammed RN, MSc, PhD; Deepak Chandran MVSc; Jawad Basit MBBS; Sandip Chakraborty MVSc; Talha Bin Emran PhD; Md. Rabiul Islam MPharm, PhD; Kuldeep Dhama PhD (SAGE Publishing, 2024)
Introduction Monkeypox (mpox) is an evolving infectious disease caused by the monkeypox virus (MPXV). On July 23, 2022, the WHO declared the recent mpox outbreaks a public health emergency of international concern (PHEIC), which terminated on May 11, 2023. As of July 11, 2023, 88,288 confirmed cases and 149 deaths have been reported from 112 countries and territories. Currently, mpox is not a PHEIC, as the outbreak and its impacts are nearly over. Nurses played significant roles during the mpox 2022 outbreak as frontline workers. Purpose In light of the impending mpox global outbreak in 2022, this brief report provides an update on the enormous difficulties faced by frontline nurses while playing a crucial role in handling the mpox outbreak and some potential solutions to these difficulties. The methodological framework employed in this narrative brief report involves conducting a comprehensive analysis and synthesis of relevant literature and hypothetical scenarios. The aim is to put forth practical strategies that can effectively tackle the difficulties encountered by frontline nurses in the context of the mpox outbreak. Additionally, the report seeks to envision a healthcare system that is more resilient in the face of future challenges. Conclusion It is important to understand the challenges the nurses face from their perspective. As frontline health care workers, the various health issues of nurses and their concerns must be taken care of appropriately by adopting optimum health service practices, adequate safety measures, recommended precautionary measures, and boosting them mentally while handling mpox patients. Counseling and the arrangement of workshops are required. Appropriate care should be taken to address the various health issues concerning nurses by adopting health service practices at optimum levels. Side by side, recommended safety and precautionary measures should be followed.